Assessment of Learned Resourcefulness, Self-Efficacy and Hope Levels of Nursing Students: A Case Study Tekirdağ - Şebnem Bilgiç; Münire Temel; Ülfiye Çelikkalp (Association of Nurse Managers, 2017)
INTRODUCTION: This study aimed to reveal learned resourcefulness, self-efficacy and hope levels of nursing students, the relationship among the levels, and the factors affecting these levels. METHODS: This descriptive research was realized with 353 students who were a Department of Nursing of a state University within the spring semestre during the Academic Year of 2015-2016. Data was collected through General Information Form, Rosenbaum Learned Resourcefulness Scale (RLRS), General Self-Efficacy Scale (GSE), and Dispositional Hope Scale (DHS) and was evaluated by using descriptive and comparative analysis. Inter-scale relationship was determined through correlation analysis. RESULTS: The average age of undergraduates was 20.87+-1.88. The average scores of undergraduates were determined to be 126.44+-16.50, 28.58+-5.79, and 25.21+-3.27 for RLRS, GSE and DHS respectively. Average scores of RLRS, GSE and DHS were found out to be significantly higher (p<0,05) for those who have experienced a traumatic incident. The average of RLRS, GSE and DHS scores were determined to be significantly higher (p<0,05) for undergraduates who have not experienced severe arguments and fights in their families. When the relationship of DHS, RLRS, and GSE was analysed, it was found out that there was a positively moderate level of relationship among them, whereas the relationship between RLRS and GSE was determined to be a positively low level relationship. DISCUSSION AND CONCLUSION: The result of this study revealed that experiencing traumatic incidents and severe inter-family arguments and fights had a significant effect on learned resourcefulness, self-efficacy and hope levels for undergraduate nursing students. It was also found out that the higher their learned resourcefulness level is, the more their self-efficacy and hope levels increase.